Herman Dooyeweerd e a construção dos problemas da crítica transcendental do pensamento teórico - Costa, Israel Pacheco da (2023)
The transcendental critique of Herman Dooyeweerd proposes to investigate the structure of theoretical thought itself in order to unveil its foundations. The result of such a critical inquiry is the discovery of the religious nature of the foundations of theoretical thought. In this sense, for Dooyeweerd, the Western philosophical tradition is marked by the dogma of the autonomy of thought, which asserts that theoretical thought is autonomous in relation to religion. Most commentators attribute the development of Dooyeweerd's transcendental critique to the neo-calvinist tradition, of which Dooyeweerd was a self-conscious follower, and to Kant's critical philosophy. However, upon a closer examination of the nuances of transcendental criticism, such an interpretation proves to be incomplete from a philosophical standpoint. Hence, this study proposes to investigate the transcendental criticism by tracing the construction of its problems, considering moments not sufficiently highlighted by the main commentators, namely: that there is a continuity between Dooyeweerd's youthful philosophy of the 1920s and his mature philosophy, which culminates in the transcendental criticism itself, and in this process, Marburg Neo-Kantianism, not Kant, exerts the fundamental influence in establishing the problems of criticism. For this purpose, methodologically, we will follow the following itinerary: in the first chapter, we briefly discuss the life and work of Dooyeweerd and present the basic ideas of the neo-calvinist tradition, followed by considerations on the state of Dooyeweerdian research and the presentation of the dissertation’s hypothesis. Next, Marburg Neo-Kantianism is presented. Three specific topics guide our exposition: the Marburgers conception of philosophy, of science, and their relation to history. In the third chapter, we delve into Dooyeweerd's thought up to 1930, paying special attention to the Normatieve Rechtsleer manuscript of 1922, which contains the epistemological problem of Dooyeweerd's early thinking, the solution to which culminates in transcendental criticism itself. Next, we present Dooyeweerd's transcendental critique in its general lines in two moments: first, we elucidate Dooyeweerd's analysis of theoretical thought in its formal structure, revealing the religious nature of the foundations of thought; shortly after, we present the further development of transcendental criticism, especially the articulation of the theory of basic religious motives, which mediate the formal religious presuppositions of thought with the historically determined dimension of culture. At this point, we will see how the transcendental critique of theoretical thought unfolds into a transcendental critique of culture, following a movement similar to that of Neo-Kantian philosophy.